"Woman, where are they?" John 7:53-8:11 and stigma in the context of HIV and Aids - Chitando, Ezra; Togarasei, Lovemore (Missionalia : Southern African Journal of Mission Studies, 2008)
The war against the devastating effects of HIV and Aids continues to be waged on different fronts. From a medical perspective, the discovery of anti-retroviral drugs should be considered a breakthrough, as it has given life to those whom society had considered 'dead'. However, for people living with HIV and Aids, one of their greatest challenges now is stigmatisation. This is particularly so when the person living with HIV and Aids is a Christian. It is in this context that this article discusses the problem of stigmatisation, suggesting a contextually relevant reading and exegesis of John 7:53-8:11. The article argues that the passage provides valuable insights regarding de-stigmatisation in the context of HIV and Aids.
Paid